Gender differences in attitudes towards information technology among Malaysian student teachers: A case study at Universiti Putra Malaysia - Wong, Su Luan; Atan, Hanafi (International Forum of Educational Technology & Society, 2007)
This article presents a quantitative study on gender differences in attitudes toward the usage of Information Technology (IT) related tools and applications. The study was conducted at Universiti Putra Malaysia, Malaysia, with 73 female and 29 male student teachers involved as participants. They were each presented with a questionnaire to relate their attitudes toward IT before and after undergoing a discrete IT course for the duration of one semester (14 weeks). The attitudes of the respondents were measured in terms of three dimensions, namely, usefulness, confidence and aversion. There were no significant differences between female and male student teachers when the pre- and post-test mean scores were compared. Both genders exhibited the same levels of attitudes before and after undergoing the comprehensive IT course. This suggests that the exposure to IT did not contribute to any significant gender disparity. The paired sample t-test results showed improved attitudes toward IT usage in both females and males after the exposure to IT. The biggest improvement for both females and males was in the aversion dimension which showed that their initial strong dislike toward IT was greatly reduced at the end of the course. In terms of confidence, female participants exhibited an enhanced confidence level after the course as opposed to the male participants. The results support the view that computer experience is gender-based as the increase in IT confidence over time assumed different patterns for females and males.